Pengembangan Model Ontologi Pada Sistem Informasi Bahasa Bali - Mahendra, I Made Yoga; Pramartha, Cokorda; Suputra, I Putu Gede Hendra; Widiartha, I Made; Wibawa, I Gede Arta; Supriana, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Balinese is the language of communication for the Balinese ethnic community. The Balinese language has a coarse to fine vocabulary called anggah-ungguhing basa Bali. The Balinese language is increasingly being abandoned by the younger generation of Bali. To help overcome these problems, the Balinese language needs to be built using the Balinese language system using the concept of a semantic ontology. The ontology development method used is Methontology and produces a consistent and valid ontology. The system built will be able to provide information about Balinese words. The system features semantic browsing, semantic search, and opposite words. To ensure system functionality, Black-Box testing was carried out. The result is that the system has good functionality.